Development of Zine Medium for German Learning with Familie Theme - Novita Ayu Permatasari (Universitas Negeri Malang, 2020)
This research aims to produce zine media which can be used as an alternative learning media. This research conducted by using ADDIE development model that includes five stages of development, such as 1) analyze, 2) design, 3) develop, 4) implementation, and 5 ) evaluate. This zine media has been conducted through the validation stage by material expert and media expert. The research results in this development can be used as an alternative learning media in German learning activities with ‘Familie’ theme and train the students to develop their writing skills.